Production of stigmasterol enriched extracts by supercritical fluid extraction of vegetable biomass - Martins, Pedro Flores (2015)
The production of stigmasterol enriched extracts from two different vegetal raw materials, Eichhornia crassipes and Moringa oleifera was assessed in this work, targeting at process optimization and economic analysis through supercritical fluid extraction (SFE) Regarding E. crassipes, the optimization of the operating conditions aimed at obtaining the best combination of pressure and ethanol content that maximizes total extraction yield, total sterols extraction yield and total and individual sterols concentration in the extract. In the range of operating conditions studied (200-300 bar and 0.0-5.0% (wt.) ethanol content),the optima were found for 300 bar and 5% ethanol for total extraction yield, amounting 1.24%; and 300 bar and 2.5% ethanol for both total sterol yield and total sterols concentration, . As to disclose the rate determining step of the extraction process, six extraction curves were measured for different flow rates and ethanol content, and three simplified phenomenological models were adjusted to the experimental data, with models based in diffusion controlled assumptions providing the best fitting adequacy. For the SFE of Moringa oleifera seed oil, a techno-economic study encompassing the coproduction of oil and sterols was accomplished using the RSM-COM approach, where the costs of drying of the biomass and separating the sterols from the bulk oil were taken into account besides the supercritical fluid extraction expenses. For a SFE unit comprising two-extractors of 1 m3 capacity and operating under optimum pressure and time conditions of 350 bar and 1.3 h, respectively, the cost of manufacturing (COM) of the oil was estimated to be 2.64€ kgoil−1. For the coproduction of a sterols mixture with 89.4 wt. % purity, the minimum COMsterols= 5.11€ kgsterols−1. The overall annual production of oil and sterols under these conditions is 558.9 tons and 1.9 tons, respectively. The most favorable net income of the studied process reaches 15.94M€ year−1, showing the proposed integrated process to be feasible, and that non negligible cost synergies exist. In the whole, the study opens the way to exploit these raw materials by supercritical fluid extraction within the scope of biorefinery premises.